Nudging smallholders to integrate more legumes into their farms - a farm model quantification - Lairez, Juliette; Gandon, Francisca; Berre, David; Falconnier, Gatien N.; Bruelle, Guillaume; Affholder, François (2024)
The increase in both income and food security of smallholder farmers in low-income countries is challenged by unpredictable weather and economic changes. Protecting the ecosystems that support farm long-term productivity, is one additional constraint, as smallholder farmers often have to prioritize short-term goals over long-term environmental concerns. Ensuring the sustainable development of smallholder agriculture, meaning meeting current human needs without jeopardizing the ability of future generations to meet their own, is challenged by low productivity of annual cropping systems, that limits substantial increase in income and food security Giller et al. (2021). Agroecological intensification is portrayed as a promising way to reconcile increase in productivity and environmental preservation. Yet, its implementation is limited by the availability of workforce, and can generate trade-offs between longterm environmental benefits and short-term farmers’ goals (food security with staple crop, cash crop with secured market). Integrating more legume crop into farming systems is one typical pathway through agroecological intensification. Legumes ensure key provision ecosystem services, as well as regulating services when it comes to climate, pest and diseases (Ditzler et al., 2021). Legume production contributes to the provision of quality food and feed. Including legumes into cropping system brings nitrogen through biological fixation. This limits the need to produce and apply mineral fertiliser, and the associated greenhouse gases emission (Cai et al., 2018). Rotating cereals with legumes breaks the growing cycle of weeds, pest, and disease. This contributes to reduce the need for pesticides on cereal (Ripoche et al., 2021). However, in land constrained environments of global South, integrating more legume in sole cropping means replacing currently grown staple or cash crops by legume crops or cultivating a fallow land. Therefore, including more legume in the farming systems competes land, and may as well compete for labour. Subsidising legume production, for the ecosystem services they deliver, may be one option to increase their share in farm cropland. However, effects of this incentive on land allocation may differ across farm types and site, depending on climate and socio-economic context. The productivity gap between legume and cereal can be lower in more sub-humid climates, or the level of market integration of farmers can change the trade-offs between the short-term and long-term goals of farmers. In this study, we want to leverage existing detailed farm data in four contrasting case studies in the Global South to explore the following questions: • Given current market conditions, why is legume share of cropland low in most farmers’ cropland? What constraints their flexibility to expand legume cultivation? • What amount of subsidy for legume cultivation is required to lift up the share of legume in the cropland, in order to bring additional ecosystem services, without compromising farmers current objectives? • How does the subsidy amount vary per farm type and across sites in smallholder context?